Exploring necroptosis: mechanistic analysis and antitumor potential of nanomaterials - Jiaheng Dong; Jiale Zhang; Kunhou Yao; Xiao Xu; Yaqi Zhou; Lei Zhang; Changjiang Qin (Cell Death Discovery)
Abstract Necroptosis, a non-apoptotic mode of programmed cell death, is characterized by the disintegration of the plasma membrane, ultimately leading to cell perforation and rupture. Recent studies have disclosed the mechanism of necroptosis and its intimate link with nanomaterials. Nanomedicine represents a novel approach in the development of therapeutic agents utilizing nanomaterials to treat a range of cancers with high efficacy. This article provides an overview of the primary mechanism behind necroptosis, the current research progress in nanomaterials, their potential use in various diseases—notably cancer, safety precautions, and prospects. The goal is to aid in the development of nanomaterials for cancer treatment.